Mecanismos kaldorianos del crecimiento regional: Aplicación empírica al caso del ALADI (1980 - 2007) - Christine Carton Madura (Colegio de Economistas de A Coru\~na, 2009)
– According to Kaldor (1970), regional growth patterns arise from a cumulative causation process as broadly combining two substantial mechanisms i.e. a productivity regime, known as the 'Kaldor-Verdoorn' law, and a demand regime due to the expansion of exportations. This paper attempts to assess empirically the Kaldor's framework in characterizing economic growth for 11 ALADI countries from a panel data set over period 1980 to 2007. After having controlled industrial heterogeneity, the results are indicating the existence of two regional trends within member states, especially in terms of external demand constraint. It can be pointed out a group of countries for which the link between productivity gains and demand growth has become weaker, due to an increasing external dependence as well as a detrimental competitive position. Finally, findings are quite conclusive insofar as the existence of the Kaldorian mechanisms is corroborated in explaining trajectories of ALADI countries while both increasing returns to scale and demand led growth are seemingly playing a significant role in the region.
Keywords: 330; ALADI; causalidad; crecimiento; exportaciones; Ley de Kaldor-Veldoorn; Método de Momentos Generalizados; panel; Regionales Wachstum; ALADI-Staaten